Notch stress analysis and fatigue strength assessment of tube-flange welded joints under torsion loading. (15th August 2019) - Hu, Yaoyu; Yan, Renjun; Shen, Wei; Liu, Kang
Abstract: A simple method named singularity length method (SLM) with a key parameter singularity length 'as' is proposed to estimate the shear stress distribution at the V-notch corner. For tube-flange welded joints (TFWJs) with 135° weld toe notches, the singularity length 'as' is observed to be determined by different geometries and is summarized into concise formulas. A rapid calculation method of the mode III notch stress intensity factor (NSIF K 3 ) without any FEA process is presented based on the SLM. Good agreement is showed between the fine meshed FE, the coarse meshed FE for the strain energy density (SED) and the proposed method. Six fatigue tests data of TFWJs is collected to conduct fatigue strength assessments based on the nominal shear stress and the rapidly-calculated NSIF K 3 . The results shows the NSIF K 3 can be well applied as a fatigue parameter. Highlights: Proposed a simple evaluation method for shear stress distribution of tube-flange welded joints. Presented a rapid calculation method of the mode III NSIF. Fatigue assessment based on the rapidly-calculated NSIF.